Anayasa Mahkemesi ve cinsiyet - Koçak, Murat (My University, 2019)
Anayasa Mahkemesi’nin cinsiyete bakış açısını gösteren birçok kararı bulunmaktadır. Bu kararların sentetik bir biçimde ele alınması ve bu incelemeden yola çıkılarak kararların rasyonel olarak yeniden inşa edilmeye çalışılması, çalışmanın özetini oluşturmaktadır. Anayasa Mahkemesi kararları cinsiyet yönünden ikili bir tasnife tabi tutulmuştur. Birinci tasnif ölçütü birey iken (bireysel özerklik); ikinci tasnif ölçütü bu alandaki devlet yükümlülükleri (korumacı/ koruyucu yaklaşım) olmuştur.

The Constitutional Court has various decisions that demonstrate its point of view about gender. The synthetic discussion of these decisions and the attempt to rationally reconstruct these decisions based on this discussion constitute the summary of the thesis. The Constitutional Court decisions have been classified in two categories. While the criterion of the first category is the individual (personal autonomy); the criteria of the second category are the liabilities of state in this area (protective approach).
Keywords: Anayasa mahkemeleri; Anayasa Mahkemesi Kararları; Bireysel Özerklik; Cinsiyet; Constitutional courts; Gender; Hukuk; Korumacı/ Koruyucu Yaklaşım Sex; Law; Personal Autonomy; Protective Approach; Sex; The Constitutional Court Decisions; Toplumsal Cinsiyet